Limitações do holismo confirmativo na matemática - Ronaldo Pimentel (2017)
Confirmational holism is the thesis that any statement of science can be confirmed or refuted, direct or indirectly, by observation. Confirmational holism also admits that mathematics can be revised from some refutation by an empirical test. The aim of this work is to show the limitations of this thesis in the field of philosophy of mathematics. Generally, Holism is well accepted in scientific theories, though, when we confront this thesis with the mathematical practices and moments of scientific discoveries, it shows that mathematical theories own more structure than the scientific vocabulary can interpret. It was exposed the various senses of analyticity in philosophy of mathematics, because analyticity can vary among philosophers, but without set aside the a priori character of mathematics. It was also exposed the various senses of holism to circumscribe the discussion around confirmational holism. After this exposition of concepts, it is followed a philosophy of mathematics centered in structures that can reject this confirmational holism.